WORKSHOP PERAN REMAJA DALAM PENANGGULANGAN HIV AIDS MENUJU ELIMINASI 2030 - Tutik Lestari; Fathiyah Suma; Mudini Muhlis; Rivai Bustamin (Jurnal Bakti untuk Negeri, 2023)
The government has put together a strategy to stop the spread of HIV AIDS both at the central and regional levels. One of the prevention efforts that must be done together by all levels of society is health education, especially in the youth group. Adolescents are the focus of all strategies to combat its spread and are the most vulnerable group to HIV AIDS infection. Objective: to increase knowledge and influence the attitudes of teenagers in efforts to prevent and combat HIV AIDS. Method: using the lecture and discussion method conducted at the Royal Resto Function with a total of 33 participants. Results: the average participant was able to answer correctly regarding HIV AIDS and the role of teenagers as peer educators. Conclusion: teenagers understand their role in efforts to prevent and combat HIV AIDS towards elimination by 2030.